Peran Kelompok Nelayan dalam Kegiatan Pariwisata terhadap Peluang Usaha dan Kerja - Fadil Arfianto; Amiruddin Saleh (Jurnal Penyuluhan, 2013)
The purpose of this study was to analyze the role of fishermen in the tourism activities of the business and employment opportunities. This study also examines the relationship between the characteristics of the group members and group elements with the role of fishermen, where the research was conducted on a group cruise boat belonging to the Organization of Boat Cruise Pangandaran (OBCP) Pangandaran Village. On testing the characteristics of group members to the role of fishermen, there was a real relationship. In the test group elements with the role of fishermen, there was a real relationship unless the relationship norms/rules of the group with the group supporting service units were not real relationships. Finally, in testing the role of fishermen and businesses and employment opportunities, there was a real relationship, this was evidenced by the presence of several members of the group who has other business other than as a fisherman or a boat cruise as homestays, restaurants and stalls.Keywords: tourism, fishing groups, businesses or work